Gerenciamento de rede com a ferramenta phpIPAM - Dias, Lucas da Silva (2020)
With the rapid growth of companies, it is necessary to take measures to facilitate the management and the process of using assets, as well as, network scopes that have units. The objective of this work is to offer concepts for the organization of company IP addresses that can be done in an orderly manner, using a tool to assist the management and management of network assets, because for those who have an organized company, everything must be cataloged . If you understand better and develop a complete work, you will be shown how a network asset control and management tool works. Segmented and structured environment, show how practical improvements to build a network structure, as well as, a segmentation can contribute to an organization, see or what are open source tools and how these tools use free code in the items to be used. The costs of implementation and the next satisfactory results during use in the environment, the resources that will be used to make a tool online will be analyzed, or will be explained in a way and how best practices for the installation and execution of the data used in the application, show demos clearly and precisely as they are made as address inclusions using a background the features it allows, or includes, include geographic data for file identification, name resolution data and classification divided into organizational masses, we will also see one of the resources that most help on a daily basis that are requested by fixed IP, through the tool, where it allows us to have a control and avoid duplication of addresses within the productive environment. The result of the application mentioned in the work will be done through a sample implanted in a company, where this instrument was implanted for control and can have a great gain in the day-to-day performance in the contact requests.